2011
DOI: 10.1007/s00426-011-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

The comprehension of action-related sentences may cause interference rather than facilitation on matching actions

Abstract: This study used a dual-task paradigm to analyze the time course of motor resonance during the comprehension of action language. In the study, participants read sentences describing a transfer either away from ("I threw the tennis ball to my rival") or toward themselves ("My rival threw me the tennis ball"). When the transfer verb appeared on the screen, and after a variable stimulus onset asynchrony (SOA), a visual motion cue (Experiment 1) or a static cue (Experiment 2) prompted participants to move their han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 23 publications
8
78
3
7
Order By: Relevance
“…Research on these issues is still in its beginning. According to some proposals, temporal parameters may be crucial (Bergen, 2007;Borreggine & Kaschak, 2006;Boulenger et al, 2006;de Vega et al, 2013;de Vega & Urrutia, 2011;Nazir et al, 2008; see also Kaschak, Zwaan, Aveyard, & Yaxley, 2006;Meteyard et al, 2007; see also Bub & Masson, 2012), i.e., the type of effect may depend on the temporal overlap between mentally simulating described actions and planning actually to be performed motor actions. I will come back to the role of temporal parameters in the following, when I will consider three possible accounts of the opposite types of effect in the present experiment and the preceding studies employing the reading-by-rotating paradigm Zwaan & Taylor, 2006;Zwaan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on these issues is still in its beginning. According to some proposals, temporal parameters may be crucial (Bergen, 2007;Borreggine & Kaschak, 2006;Boulenger et al, 2006;de Vega et al, 2013;de Vega & Urrutia, 2011;Nazir et al, 2008; see also Kaschak, Zwaan, Aveyard, & Yaxley, 2006;Meteyard et al, 2007; see also Bub & Masson, 2012), i.e., the type of effect may depend on the temporal overlap between mentally simulating described actions and planning actually to be performed motor actions. I will come back to the role of temporal parameters in the following, when I will consider three possible accounts of the opposite types of effect in the present experiment and the preceding studies employing the reading-by-rotating paradigm Zwaan & Taylor, 2006;Zwaan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One important line of evidence -which also is of immediate relevance to the study to be presented in the present paper -stems from studies addressing the interaction between language comprehension and action and indicating that processing linguistic input can affect motor actions. In particular, many studies revealed an action-sentence compatibility effect (Glenberg & Kaschak, 2002), i.e., response times for sentences describing an action in a particular direction were found to be affected by whether the direction of the hand movement required for responding was compatible or incompatible to the direction implied by the sentence (e.g., Bergen & Wheeler, 2005;de Vega, Moreno, & Castillo, 2013;Glenberg & Kaschak, 2002;Zwaan & Taylor, 2006; see also Bub & Masson, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…De Vega, Moreno, and Castillo (2012) present two experiments that look at changes in motor compatibility effects during comprehension based on the relative timing of the motor response to the processing of action-relevant language. The authors show that at short stimulus onset asynchrony, the traditional motor compatibility effect is reversed: participants are faster to respond when the direction of the action in the sentence mismatches the direction of the motor response that needs to be made.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…La mayoría de las evidencias empíricas de las teorías corpóreas se basan en material concreto, evitando los investigadores el estudio del lenguaje abstracto. Así, se utilizan descripciones visuales (Stanfield y Zwaan, 2001;Zwaan, Stanfield y Yaxley, 2002;Beilock y Lyons, 2009), de relaciones espaciales (Zwaan y Yaxley, 2003a;2003b), de acciones de transferencia (Glenberg, y Kaschak, 2002;Borregine y Kaschak, 2006;De Vega, Moreno y Castillo, 2011), de acciones manipulativas, o de otras partes del cuerpo Zwaan y Taylor, 2006).…”
Section: El Problema De La Abstracciónunclassified